2021
DOI: 10.1016/j.xpro.2021.100479
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biophysical characterization of the nucleosome-binding PZP domain

Abstract: Summary The core subunit of the MORF acetyltransferase complex BRPF1 contains a unique combination of zinc fingers, including a plant homeodomain (PHD) finger followed by a zinc knuckle and another PHD finger, which together form a PZP domain (BRPF1 PZP ). BRPF1 PZP has been shown to bind to the nucleosome and make contacts with both histone H3 tail and DNA. Here, we describe biophysical and structural methods for characterization of the interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For purification of native complexes, after large-scale expansion of K562 clones, affinity purifications of tagged MORF N WT (aa 2–716), ΔWH1 (aa 86–716), ΔWH2 (aa 2–99 + aa 183–716) and ΔWH1/2 (aa 183–716), were performed on nuclear extracts as previously described 59 . Briefly, nuclear extracts were prepared following standard procedures and pre-cleared with CL6B Sepharose beads.…”
Section: Methodsmentioning
confidence: 99%
“…For purification of native complexes, after large-scale expansion of K562 clones, affinity purifications of tagged MORF N WT (aa 2–716), ΔWH1 (aa 86–716), ΔWH2 (aa 2–99 + aa 183–716) and ΔWH1/2 (aa 183–716), were performed on nuclear extracts as previously described 59 . Briefly, nuclear extracts were prepared following standard procedures and pre-cleared with CL6B Sepharose beads.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the biophysical properties of each chromosomal component, including DNA, nucleosomes, and chromatin, are essential for the analysis of such hierarchy in chromosomes. [14][15][16] Additionally, due to structural complexity and technological limitations, 1,[17][18][19][20] the question remains open as to how the human mitotic chromosomes are specically condensed at each stage, including the interphase, prophase, metaphase, anaphase, and telophase. Although extensive microscopic studies revealed the condensed supramolecular structure of metaphase chromosomes, 1,18,21 their detailed biophysical characteristics such as surface charge and nanomechanical mapping are still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Tese include the BRPF1 specifc N-terminal (BN) at the N-terminus, enhancer of polycomb (EPC) like motif 1 (EPC-1), plant homeodomain (PHD)-zinc-knuckle-PHD (PZP) module, nuclear localization signal (NLS), EPC-II, a bromodomain, and a Cterminal proline-tryptophan-tryptophan-proline (PWWP) domain [9,[11][12][13][14]. Te EPC-I and BN domains are required for binding to the MYST domain of KAT6A or KAT6B, whereas the PZP domain functions by recognizing histone H3 tails and associating them with DNA [9,[15][16][17]. EPC-II interacts with two accessory proteins, ING5 and MEAF6, while the bromodomain binds to acetyl-lysine in histone H4 and H3 (H4/H3KAc) [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%